Functional Properties of Purple Water Yam Flour Modified by Lactobacillus plantarum - Ulyarti, Ulyarti; Yulia, Ade; Nazarudin, Nazarudin; Armando, Yunta Gombang; Erawaty, Lela (Makara Journal of Science, 2021)
Purple water yam flour modified by Lactobacillus plantarum fermentation may be used as an ingredient in flour-based functional food. The purpose of this research is to determine the effect of fermentation time on the functional properties of purple water yam flour modified using L. plantarum. This research used a randomized block design with six treatments: without fermentation (control) and 12, 24, 36, 48, and 60 h of fermentation. Results showed that lactic acid bacteria initially grow well with increasing viability over 48 h of fermentation. Growth and viability rates began to decrease as the organisms entered the declining or dying phase. Statistical analysis showed that fermentation time affects the solubility at 75 °C, chromatic color values L* and b*, and antioxidant activity of flour. Fermentation for 36 h produced the best modified purple water yam flour with an antioxidant activity of 69.82%, bulk density of 0.817 g/mL, water absorption capacity of 3.31 g/g, oil absorption capacity of 1.20 g/g, solubility of 0.45%, L* of 80.33, a* of 16.33, and b* of −5.33. The results indicate that purple water yam flour modified by L. plantarum fermentation for 36 h could be developed as a functional food ingredient.